Seeing Both Sides of the Coronavirus Crisis - Jianghong Li (WZB Berlin Social Science Center, 2020)
The pandemic's impact is often said to be overall negative. But how about the positive side-effects of COVID-19?
Keywords: 300; conséquences; contagious disease; Coronavirus; COVID-19; crisis behavior; crisis management; digitalisation; epidemic; future orientation; innovation; research and development